Pengaruh Substitusi Tepung Terigu dengan Pati Umbi Garut terhadap Sifat Organoleptik dan Fisikokimia Kulit Pie - Ulfa, Masayu Nur; Daningka, Vali; Marvie, Ilham (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2025)
Sweet potato is one of the food ingredients promoted by the government for its potential to replace wheat flour, and its starch can be used as a substitute material of 50-100%. The purpose of this research is to analyze the effect of the level of preference or acceptance of panelists towards pie crust with sweet potato starch substitution and to describe the physicochemical properties and color of the pie crust. This study conducted five treatments of pie crust, namely pie crust with 100%, 75%, 50%, 25%, and control substitutions of sweet potato starch. Data analysis was performed using One Way ANOVA at a 5% significance level, followed by a DMRT test if there were significant effects. The pie crust with 75% sweet potato starch substitution was the panelists' best choice in terms of color, taste, aroma, texture, and overall. There were no significant effects found on the moisture content and fat content of the pie crust. The results for ash content, protein, carbohydrates, L color, a color, and b color of the pie crust showed significant effects.